Efecto del sulfato de zinc sobre la intoxicación experimental con Pithomyces chartarum, en novillos pastoreando Brachiaria decumbens - Aycardi B., Eduardo R.; García Durán, Obed; Lascano Aguilar, Carlos Eduardo; Salinas, José G.; Rivera, B.; Torres, B.; Bohórquez Lozano, Viviana (International Center for Tropical Agriculture, 1983)
A study was design to evalutate the effect of Pithomyces chartarum fungus on steers grazing Brachiaria decumbens, and the effect of zinc applied to the soil and added to the mineral supplement to aid in the prevention of photosensitivity. Twenty steers crossbred zebu, 10-12 months old were used for the trial. Animals with symptoms and clinical lesions of photosensitivity were found 23 days after first grazing of contaminated grass. The group of animals that grazed the paddock where zinc had been applied disease. Levels of gamma-glutamyl-transferase (G.G.T.) were used to detect clinical and sublinical disease. Zinc applied to the soil resulted in an increase of its content of 52 percent and 77 percent respectively for soil and plant tissue. The addition of zinc to the soil could become a practical system to prevent the effect of P. chartarum toxins to young cattle grazing contaminated B. decumbens or other grasses.